Non-Relativistic Phase Shifts for Scattering on Generalized Radial Yukawa Potentials. (1st April 2016) - Oluwadare, O.J.; Thylwe, K.E.; Oyewumi, K.J.
Abstract: Non-relativistic phase shifts for a generalized Yukawa potential V(r) = − V0 (e −αr /r) − V1 (e −2αr /r 2 ) are studied by the amplitude-phase method and by a frequently used analytic method based on a Pekeris-type approximation of power-law potential terms. Small variations of V1 seem to have marginal effects on the effective potential and on exact phase shifts. However, as pointed out in this study, a Pekeris-type approximation in scattering applications often implies serious distortions of both effective potentials and phase shifts. The Pekeris-type based analytic approximation in this study seems to give low-quality scattering results for this model potential at low energies.